Manajemen Inovasi Pembelaran untuk Mencapai Mutu Lulusan di SMA Bhakti Putra Cibodas - Faridah, Nendah Siti; Purwoko, Sigit Djalu (LPPM Institut Pendidikan Nusantara Global, 2024)
The aim of this research is to find out and analyze the main forms of innovation that must be implemented as well as identifying inhibiting factors in innovating learning to achieve quality graduates at SMA Bhakti Putra Cibodas. This research method uses descriptive analysis. to analyze the data objectively and describe the Management of Learning Innovations to Achieve Quality Graduates at Sma Bhakti Putra Cibodas. Data collection was carried out by means of short interviews with management staff at SMA Bhakti Putra Cibodas in order to obtain an overview of the extent to which Innovation Management has been implemented and provide evaluations and suggestions regarding the implementation of innovation management at SMA Bhakti Putra Cibodas. The research results show that at Bhakti Putra Cibodas High School, efforts continue to be made to increase learning innovation even though limited internet access is still a major challenge. The main form of innovation that must be implemented is the optimal use of internet media, even though access is not yet optimal, by providing online resources and online learning platforms. Peer tutoring is also introduced as an innovative element, strengthening collaboration in the learning environment. The application of storytelling techniques and a case study approach helps create memorable learning experiences. However, a number of inhibiting factors, including limited human resources, stakeholder resistance, and limited funding, require further attention to ensure the sustainability and effectiveness of these innovations in achieving the desired quality of graduates.